2007
DOI: 10.1016/s0030-6657(07)70493-6
|View full text |Cite
|
Sign up to set email alerts
|

Flora bakteryjna występująca na powierzchni i w miąższu migdałków w przewlekłym zapaleniu migdałków podniebiennych

Abstract: The purpose of the work was to present the frequency of isolation of particular bacterial species from smear samples obtained from the surface of the palatal tonsils and from aspirates of tonsillar core. The material involved 100 patients, 49 women and 51 men among them, who were qualified to tonsillectomy based on their history, otolaryngological examination and selected laboratory parameters and in whom bacteriological examination of smears taken from the right and left palatal tonsil were performed. The mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Streptococcus pyogenes strains were co-isolated in four patients with RT, and none were isolated in patients with a PTA. Other studies have also reported a low isolation rate (1.7–5%) of streptococci in patients with RT; streptococci have been found to be less prevalent in the tonsillar core (1.7%) [ 29 , 31 ] than on the tonsillar surface. S. pyogenes in the RT pathogenesis has most likely been overrated or, alternatively, decreased in recent years [ 2 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus pyogenes strains were co-isolated in four patients with RT, and none were isolated in patients with a PTA. Other studies have also reported a low isolation rate (1.7–5%) of streptococci in patients with RT; streptococci have been found to be less prevalent in the tonsillar core (1.7%) [ 29 , 31 ] than on the tonsillar surface. S. pyogenes in the RT pathogenesis has most likely been overrated or, alternatively, decreased in recent years [ 2 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacteremia in the patients who have experienced tonsillectomy due to chronic tonsillitis may lead to intense outcomes, especially in those who are faced with the risk of cardiovascular infection [6, 7]. Some studies have shown that the bacterial pathogens related to tonsillitis inhabited the surface and depth of the tonsil tissue [8]. Moreover, a large number of studies have presented similarities between the types of isolated microorganisms from the surface and depth of tonsil, but the degree of likeness has been very different in these studies [6, 911].…”
Section: Introductionmentioning
confidence: 99%
“…S. pyogenes strains were isolated with other microorganisms in 4 patients with RT, but not in any patient with PTA. Also, in other studies, a low (1.7-5 %) frequency of streptococci isolation in patients with RT has been found, it has been proven that they are more often found on the surface of the palatine tonsils than in the tonsils(Syryło et al, 2007;Alasil et al, 2013). The role of S. pyogenes in the pathogenesis of RT has been overestimated or has been decreased over the years(Lindroos, 2000; Zautner et al, 2010; Kostić et al, 2022).…”
mentioning
confidence: 97%